Survival Outcome of Surgical Resection vs. Radiotherapy in Brain Metastasis From Colorectal Cancer: A Meta-Analysis - Chang, Yu; Wong, Chia-En; Lee, Po-Hsuan; Huang, Chi-Chen; Lee, Jung-Shun (Frontiers in Medicine, 2022)
Background: The incidence of brain metastasis from colorectal cancer increases along with the greater survival rate for colorectal cancer, owing to the advances in therapeutic modalities. Local treatment strategies for brain metastasis include surgical resection and radiotherapy. However, given the incongruent literature, the optimal therapeutic approach remains to be investigated. The aim of this study is to systematically compare the real-world survival outcome of surgical resection and radiotherapy in patients with brain metastasis from colorectal cancer. Methods: Following PRISMA and MOOSE guidelines (PROSPERO, ID: CRD42021240200), the Cochrane Library, Embase, and Medline were searched from the database inception to August 2021. Meta-analyses were conducted with results pooled using hazard ratios with corresponding 95% confidential intervals to evaluate the overall survival following local treatment for brain metastasis from colorectal cancer. Summary effects were evaluated using a series of random-effect model. Results: Seventeen retrospective studies consisting of 1438 participants were included. In comparison with radiotherapy, the overall survival of patients who received brain metastasectomy was generally longer (HR, 0.54; 95% CI, 0.47–0.62). Extracerebral metastases (HR, 1.58; 95% CI, 1.34–1.86) and multiple brain metastases (HR, 1.38; 95% CI, 1.10–1.72) were associated with worse survival outcome. Conclusions: For patients with brain metastasis from colorectal cancer, current real-world evidence demonstrated the survival benefit of aggressive neurosurgical management in suitable patients. In addition, patients with extracerebral metastases and multiple brain metastases had worse survival outcome.